The game - Fincher, David 1962-; Golin, Steve; Douglas, Michael 1944-; Penn, Sean 1960-; Unger, Deborah Kara 1966-; Rebhorn, James 1948-2014; Mueller-Stahl, Armin 1930- (Universal Studios Home Entertainment, 2012)
"In this thriller, Nicholas Van Orton, a shrewd and successful businessman who is always in control, has been enrolled by his brother in "The Game"--"a profound life experience" with no rules, which begins quietly but soon erupts in a confusing maze of devastating events. Terrorized by forces who seem intent on dismantling all that he has built, Van Orton has to win this deadly game or lose control of everything in his life."
DVD format ; NTSC, region 1 ; 16:9 widescreen, 2.40:1 ; Dolby digital 5.1 surround. - Originally released as motion picture in 1997. - Special features include: Disc 1: Audio commentary by director David Fincher, actor Michael Dougls, screenwriters John Brancato and Michael Ferris, director of photography Harris Savides, production designer Jeffrey Beecroft, and visual effects supervisor Kevin Haug. Disc 2: Alternate ending ; Film-to-storyboard comparisons ; Behind the scenes ; Psychological test film ; Teaser and trailer. A booklet featuring an essay by film critic David Sterritt
Orig.: USA, 1997
Disc 1. Feature film (Theatrical 5.1 surround soundtrack; alternate 5.1 surround mix for home theater viewing ; audio commentary by director David Fincher, Savides, Michael Douglas, John Brancata and Michael Ferris, etc.) -- Disc 2. Behind-the-scenes footage and film-to-storyboard comparisons for four major set pieces ; alternate ending ; trailer and teaser, with commentary
Keywords: Psychological games / Drama; Businessmen / Attitudes / Drama; Brothers / Drama; Geschäftsmann; Spiel; Mystery -- Film; Thriller; Psychologie; Bruder; Film; DVD-Video